2020
DOI: 10.1177/1090198120921188
|View full text |Cite
|
Sign up to set email alerts
|

Engage for Equity: Development of Community-Based Participatory Research Tools

Abstract: We developed a set of four community-based participatory research (CBPR) partnership tools aimed at supporting community–academic research partnerships in strengthening their research processes, with the ultimate goal of improving research outcomes. The aim of this article is to describe the tools we developed to accomplish this goal: (1) the River of Life Exercise; (2) a Partnership Visioning Exercise; (3) a personalized Partnership Data Report of data from academic and community research partners; and (4) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…Our project team found that integrating PCOR and patient engagement methods with CBPR principles helped us to define a process for working together to complete meaningful work despite threats to developing and maintaining an equitable partnership. Other recent work in generating CBPR tools has also recognized the utility of integrating frameworks (Parker et al., 2020). Based on our experience, applying portions of several frameworks that offer distinct solutions to partnership challenges could make programs and research at the margin of the community and health care organizations more effective at reducing health disparities.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Our project team found that integrating PCOR and patient engagement methods with CBPR principles helped us to define a process for working together to complete meaningful work despite threats to developing and maintaining an equitable partnership. Other recent work in generating CBPR tools has also recognized the utility of integrating frameworks (Parker et al., 2020). Based on our experience, applying portions of several frameworks that offer distinct solutions to partnership challenges could make programs and research at the margin of the community and health care organizations more effective at reducing health disparities.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Because we (the authors) thought river metaphors could be helpful in communicating across such a diverse group-which included participants from rural communities and cities, community-based organizations and NGOs, and Spanish and Quechua speakers (all spoke Spanish, but some spoke more fluently in Quechua)we incorporated "River of Life (RoL)" method (see Wallerstein & Auerbach, 2004;Parker et al, 2020,) into the systematization of our planning process. Specifically, we asked participants to record on index cards the most significant moments and actions from their participation in the BD regional planning process and subsequent program implementation (a 3-year period from 2012-14 approx).…”
Section: River Of Life As a "Systematized" Expression Of Our Shared Pmentioning
confidence: 99%
“…To build on and expand our nascent understanding of how partnerships successfully worked together to achieve their outcomes, the current study, Engage for Equity (E2), sought to not only refine but extend previous RIH measures. We also conducted an intervention trial of workshops compared with online resources to strengthen power sharing and collective empowerment practices toward partnerships' desired outcomes (Dickson et al, 2020;Parker et al, 2020;Wallerstein et al, 2020). We hypothesized (and sought to create a new measure of) "Collective Empowerment," as a key driver of both structural and relational pathways to partnership outcomes, building from the community empowerment definition of people participating collectively, embracing core values for social change, and engaging in Freirian critical reflection and action to gain control over their lives (Allen et al, 1989;Freire, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on psychometric results from the previous study (Oetzel et al, 2015), community consultations (Belone et al, 2016), and consultation with a national advisory group of community and academic researchers (Wallerstein et al, 2020), we included new subscales (n = 5), shortened longer subscales (n = 5), made major revisions to or dropped several subscales (n = 5), and made minor revisions to enhance readability of other subscales (n = 4). The result was seven major scales (with 23 subscales) corresponding to the domains of the CBPR conceptual model: contextual capacity, commitment to collective empowerment, relationships, community engagement in research actions (CERA), synergy, partner and partnership transformation as part of intermediate systems and capacity changes, and longer-term projected outcomes.…”
Section: Introductionmentioning
confidence: 99%